Assessment of growth ability and removal efficiency of the Hydrilla (Hydrilla verticillata) in wastewater - Chonyitree Sangwijit; Nitikorn Phoosuwan; Prapagon Sangwijit; Watcharapong Thakong; Laksanawadee Saikhao (Egyptian Journal of Aquatic Research, 2022)
The present quasi-experimental research investigated the growth ability and removal efficiency of Hydrilla verticillata in freshwater from Nong Han Lake (NHL), domestic wastewater from constructed wetlands (CW) and wastewater from university canteen wastewater (UCW) in Sakon Nakhon, a north-east province in Thailand. The growth rate was measured by evaluating the fresh mass of H. verticillata and comparing the removal efficiency of the biochemical oxygen demand (BOD), the chemical oxygen demand (COD) and phosphate at the hydraulic retention time on days 7, 14, 21 and 28. The efficiency of BOD removal of H. verticillata in UCW, NHL and CW was 26, 80 and 84%, respectively, whereas the COD removal efficiency was 25, 72 and 63%, respectively, and that of phosphate was 6, 44 and 87%, respectively. No difference was found in growth rates between H. verticillata from NHL and CW. Further, CW provided a good growth rate of H. verticillata, and the domestic wastewater discharges could provide a rapid growth of H. verticillata. Finally, H. verticillata might be used in aquatic ecosystems.